Model-centered learning pathways to mathematical understanding using GeoGebra - Bu, Lingguo; Schoen, Robert C. (Robert Clarence) 1975- (Modeling and simulations for learning and instruction, 2011)
Model-Centered Learning: Pathways to Mathematical Understanding Using GeoGebra is the first book to report on the international use of GeoGebra and its growing impact on mathematics teaching and learning. Supported by new developments in model-centered learning and instruction, the chapters in this book move beyond the traditional views of mathematics and mathematics teaching, providing theoretical perspectives and examples of practice for enhancing students' mathematical understanding through mathematical and didactical modeling. Designed specifically for teaching mathematics, GeoGebra integrates dynamic multiple representations in a conceptually rich learning environment that supports the exploration, construction, and evaluation of mathematical models and simulations. The open source nature of GeoGebra has led to a growing international community of mathematicians, teacher educators, and classroom teachers who seek to tackle the challenges and complexity of mathematics education through a grassroots initiative using instructional innovations. The chapters cover six themes: 1) the history, philosophy, and theory behind GeoGebra, 2) dynamic models and simulations, 3) problem solving and attitude change, 4) GeoGebra as a cognitive and didactical tool, 5) curricular challenges and initiatives, 6) equity and sustainability in technology use. This book should be of interest to mathematics educators, mathematicians, and graduate students in STEM education and instructional technologies